Birds of Santa Teresa, Espírito Santo, Brazil: Do humans add or subtract species? - Willis, Edwin O. [UNESP]; Oniki, Yoshika [UNESP] (My University, 2002)
In uplands and lowlands of Santa Teresa, central Espírito Santo State, Brazil, 405 bird species were confirmed by field, museum, and literature studies. Of these, 16 seem to have disappeared, while 67 other species seem to have been lost from the lowlands (where no large biological reserves exist). Due to a suggestion that human areas add species to beta-diversity, we verified that up to 79 species now present have perhaps invaded with human activity (and 10 others are likely to invade), a total similar to that for lost species. However, lost species are often rare and invading species often widespread, resulting in exchange of Picassos for Coca-Cola bottles. Furthermore, gains exceed losses only when large biological reserves are present, as in the uplands (Nova Lombardia, Santa Lucia Reserves, each with over 250 species). Small or irregular reserves usually lose well over half their species, and these are only partly replaced by the invaders, resulting in net losses of up to half the local avifaunas. If one lists only 31 probable invaders, rather than a possible 79, things are even worse; net losses occur even in the entire township and near reserves, reaching over 200 species around lowland private reserves. Future productive development of human areas can eliminate or maltreat many invading species, too. While approving taxes on improductive use of land, as it leaves other areas free, we suggest that many current local uses, such as for coffee, are luxury production and could, be taxed.
Keywords: Atlantic forest; Avifaunas; Beta-diversity; Biodiversity; Biogeography; Biological reserves; Espírito Santo; Luxury tax; Productivity